ENVIRONMENTAL SANITATION AT HOME AND HISTORY OF INFECTION DISEASES AS RISK FACTORS FOR STUNTING IN TODDLERS IN DROKILO VILLAGE, KEDUNGADEM DISTRICT, BOJONEGORO REGENCY - Aimmatus Shofifah; Lilis Sulistyorini; Sarva Mangala Praveena (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Stunting is one of the nutritional issues that becomes the triple burden of malnutrition and affects the world, especially in almost every nation. Indonesia is listed as the third country with the greatest stunting prevalence in the Southeast Asia/South-East Asia Regional (SEAR) areas. This study aimed to examine the connections between stunting incidence a history of infectious diseases, as well as the connections between toddlers who experience stunting events a history of infectious diseases among toddlers in Drokilo Village. Methods: This study used a case-control research design and an analytical observational approach. It involved 51 toddlers samples and included dependent variables i.e., stunting incidence and independent variables i.e., environmental sanitation at home and a history of infectious diseases. Bivariate analysis was utilized together with Chi-square test to examine the variables. Results and Discussion: Male toddlers over the age of two years frequently experienced stunting. With a p-value of 0.046, environmental sanitation at home was associated with a lower stunting incidence. With a p-value of 0.037, a history of infectious diseases was associated with higher stunting incidence. Conclusion: Environmental sanitation at home a history of infectious diseases had significant relationships with stunting incidence in toddlers. In short, these two factors may cause stunting in toddlers in Drokilo Village, Kedungadem District, Bojonegoro Regency.